Long-covid cognitive impairment: Cognitive assessment and apolipoprotein E (APOE) genotyping correlation in a Brazilian cohort - Tavares-Júnior, José Wagner Leonel; Oliveira, Danilo Nunes; da Silva, Jean Breno Silveira; Feitosa, Werbety Lucas Queiroz; Sousa, Artur Victor Menezes; Cunha, Letícia Chaves Vieira; Gaspar, Safira de Brito; Gomes, Carmem Meyve Pereira; de Oliveira, Laís Lacerda Brasil; Moreira-Nunes, Caroline Aquino; Montenegro, Raquel Carvalho; Sobreira-Neto, Manoel Alves; et al. (Frontiers in Psychiatry, 2022)
Introduction: Few studies have objectively evaluated cognitive deficits after acute phase of disease of COVID-19. Moreover, the role of APOE genotypes on cognitive decline on patients with COVID-19 has not been evaluated yet. Methods: This cross-sectional study was conducted with confirmed COVID-19 patients with a neurological symptom that persisted for more than three months from onset. APOE genotypes were determined. Results: The final sample consisted of 141 patients. The most frequent APOE genotype was E3/E3 (N = 95; 67.3%). Ninety-three patients (65.9%) had memory impairment symptoms as the main complaint, objectively confirmed through screening tests in 25 patients (17.7%). Patients with cognitive impairment had a lower frequency of anosmia in comparison with Normal and subjective cognitive deficits (SCD) groups (p=0.005). Depression was also more frequent in CI group and SCD (p=0.046). Cognitive impairment was significantly more frequent in hospitalized patients and those with lower level of scholarity. Cognitive status had no association with APOE genotype. Discussion: Hospitalized patients present a more severe infection with greater possibility of systemic complications, greater inflammatory response and prolonged hospitalization which could impact cognitive performance. Cognitive impairment in COVID-19 patients do not necessarily involve specific APOE polymorphisms. However, psychiatric disorders may also be responsible for cognitive complaints. Conclusion: Cognitive complaints are frequent in COVID-19 patients, even after disease acute phase and in mild cases. Hospitalized participants and depressive patients may have a higher risk of cognitive impairment. APOE genotype or haplotypes may not significantly play a role on COVID-19 cognitive impairment.